Developing Tutorials for Several Institutional Partners: A Real Challenge! | Développer des tutoriels pour plusieurs institutions partenaires : un réel défi ! - Brigitte Belzile (The Canadian Network for Innovation in Education (CNIE), 2015)
This case describes the two-year development of a set of interactive tutorials for students and faculty at a number of community colleges and one university in order to target information literacy skills among their students, primarily searching for and evaluating information found online. The tools created were published under a Creative Commons license and made available to faculty members and instructors for the purposes of both online and classroom delivery. The main problems encountered dealt with collaboration issues arising between participating institutions, the availability and skill sets of the main contributors and the beta testing of materials developed for the target clientele.